2002
DOI: 10.1016/s0167-4889(02)00328-2
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid, quercetin, differentially regulates Th-1 (IFNγ) and Th-2 (IL4) cytokine gene expression by normal peripheral blood mononuclear cells

Abstract: Flavonoids are plant metabolites that are dietary antioxidants and exert significant anti-tumor, anti-allergic, anti-inflammatory and anti-viral effects. It is generally accepted that Th-1 derived cytokines such as IL-2, IFNgamma and IL-12 promote cellular immunity while Th-2 derived cytokines such as IL-4, IL-5, IL-6 exert negative immunoregulatory effects on cellular immunity while upregulating humoral immunity. The molecular mechanisms underlying the biological activities of flavonoids have not been elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 14 publications
5
127
2
3
Order By: Relevance
“…The lacking differences in cytokine IFN-g production are in agreement with those described by Jacob et al (2008) in humans for a combination of lycopene and vitamin C. On the contrary, quercetin added to cell cultures showed a dose-dependent upregulation of gene expression; thus, increasing IFN-g production (Nair et al, 2002). All these divergent results might be due once again to different doses of flavonoids used in these studies.…”
Section: Antioxidant Parameterssupporting
confidence: 89%
“…The lacking differences in cytokine IFN-g production are in agreement with those described by Jacob et al (2008) in humans for a combination of lycopene and vitamin C. On the contrary, quercetin added to cell cultures showed a dose-dependent upregulation of gene expression; thus, increasing IFN-g production (Nair et al, 2002). All these divergent results might be due once again to different doses of flavonoids used in these studies.…”
Section: Antioxidant Parameterssupporting
confidence: 89%
“…The same compound also inhibits the cytotoxic effect of cytotoxic T-cells (Schuwartz et al, 1982). Recently, quercetin was also demonstrated to enhance interferon (IFN)-γ production, but inhibited interleukin (IL)-4 production, suggesting a suppressive action of humoral immunity (Nair et al, 2002). However, no report has been available to describe the in vivo effects of quercetin on antibody production, and to our knowledge this is the first report showing the inhibitory activity of quercetin on antibody production in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Though the underlying mechanism(s) whereby EAE boosts the haematological indices of P. hypophthalmus is not properly understood, nevertheless, Nair et al (2002) and Lyu and Park (2005) have suggested that flavonoid plant metabolites in the bulbs of E. americana (Kuntorini et al 2016) may contribute to promoting cellular immunity by modulating Th-1 derived cytokines such as IL-2 (Interleukin 2) and INFγ (Interferon). Flavonoids found in the EAE may be biocatalysts in the production of leukocytes and in stimulating nonspecific cellular immunity by leukocytes.…”
Section: Discussionmentioning
confidence: 99%